ENVIRONMENTAL CHANGES AND TIMING OF EVENTS DURING THE CRETACEOUS-PALEOGENE TRANSITION: ASSESSING CONSEQUENCES OF DECCAN VOLCANISM AND THE CHICXULUB IMPACT - Mateo Fernandez Caso, Maria Paula (Princeton, NJ : Princeton University, 2017)
The end-Cretaceous mass extinction has been popularly associated with the Chicxulub impact on Yucatan whereas Deccan volcanism in India was considered a distant possibility due to its presumed duration over millions of years. However, the role of the impact during the mass extinction is still questionable based on evidence of Chicxulub predating the KPB, already stressed environments before the mass extinction and delayed faunal recovery after. In addition, recent advances on Deccan volcanism confirmed the main phase of eruptions led to high stress environments during the last 250 kyr before the mass extinction, placing further doubt on Chicxulub impact as the sole cause for this biotic crisis. This thesis contributes to this debate by focusing on the timing and nature of environmental changes that affected marine ecosystems before, during and after the mass extinction based on a multidisciplinary approach including quantitative planktic foraminiferal biostratigraphy, geochemistry, mineralogy and sedimentology. Two chapters deal with the Chicxulub impact evaluating relative age and nature of impact spherule deposits. In the North Atlantic, discrete intervals of disturbed sediments with impact spherules, previously interpreted as impact-induced mass wasting deposits at the KPB, were found above a major KPB hiatus, reworked into the early Danian (Chapter 3). In the Eastern Pacific (Colombia), pristine impact spherules, previously interpreted as primary Chicxulub fallout, were also found above a KPB hiatus, reworked within early Danian sediments (Chapter 4). These new results are consistent with previous observations of Chicxulub impact spherules reworked in early Danian sediments as a result of Gulf Stream and tectonic activity. Two chapters deal with the environmental effects of Deccan volcanism. Chapter 1 documents Maastrichtian climate and faunal upheavals that led to the mass extinction, in the Indian Ocean, Tethys and South Atlantic, and proves a direct link to volcanism. Chapter 5 evaluates Deccan volcanism and the delayed recovery after the mass extinction as well as Dan-C2 warming in the early Danian. Results show delayed recovery due to continued volcanic eruptions after the mass extinction and full recovery only after volcanism ended. The Dan-C2 event, previously attributed to Deccan volcanism, requires further evaluation due to age uncertainties.